Implementasi Maqashid Syariah dalam Regulasi dan Kebijakan Ekonomi Islam di Indonesia: Perspektif Teoritis dan Praktis - Halla Tiaranissa; Nailatul Fitriah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study explains how Maqashid Sharia is applied in regulatory and Islamic economic policies in Indonesia through the implementation of five fundamental principles: protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal). This concept is proposed as a normative foundation for formulating and implementing public policies that are just, sustainable, and focused on welfare. The article discusses the application of Maqashid in Islamic finance, banking, internet regulation, consumer protection, and the role of ZISWAF institutions. The author also identifies challenges in implementation, such as limited human capacity in understanding Maqashid, regulatory conflicts, and fragmented policy interventions. The recommendations highlight the importance of promoting Maqashid literacy, regulatory reform, and institutional synergy as strategies to build an Islamic economy rooted in spiritual ethics and social justice.